The impact of government debt on economic growth in Malaysia - Cheong, Hong Seng; Lee, Shao Xi; Lim, Qing You; Tan, Xue Thing; Yee, Li Xian (2022)
The COVID-19 pandemic has affected the economy of Malaysia since any type of movement control order is still implemented by the government, and it caused most businesses and companies to be forced to suspend operations, which caused the economy to decline. Before the pandemic, the significant rise in public debt in recent years was partly owing to the current government's goal of making Malaysia a high-income and developed country by 2020. In 2021, the Malaysian government decided to lift the government debt ceiling from 60 percent to 65 percent and asked for agreement from Malaysia's Parliament, in order to raise funds for improving economic growth during the pandemic period. Even though the amount of public debt Malaysia owes is still judged as reasonable, it may impede the growth and achievement of the targets of economic reform in Malaysia. The uncertainties regarding national debt service obligations discourage people from seeking economic change in Malaysia. This research investigates the relationship between government debt and economic growth in Malaysia using quarterly observations from 2010Q1 to 2019Q4. The dependent variable is the Real Gross Domestic Product (GDP) of Malaysia, while the independent variables include budget deficit, government expenditure, and external debt. In order to fulfill the research objective, an ordinary least-square (OLS) model will be applied to determine the relationship between government debt and economic growth. The results show the negative impacts of the budget deficit and external debt on the Real GDP, while government expenditure has a positive impact on the real GDP. The findings determine that huge government expenditure could lead to higher economic growth but not spending greater than government revenue, as a deficit leads to economic contraction. Higher external debt also negatively affects economic growth as well. In addition, the Newey-West Method is used to solve the autocorrelation issue in the model. The Malaysian government should control the usage of funds wisely, including tax revenue and internal debt, and provide more subsidies and initiatives for Malaysians to empower people and stimulate the economy.